Fields and Registers of Management Accounting - Mackevičius, Jonas (Ekonomika, 2001)
Terms and definition. of management accounting are critical estimated in the article. Especially great importance is attached for differences and common traits between financial and management accounting. Schemes of connection of management accounting witch cost and production accounting are presented. It is proved that there is not yet determinates the accounting field of management accounting, i. e. that fields which must investigate management accounting.